AWARENESS TOWARDS TYPE 2 DIABETES MELLITUS IN URBAN POPULATION OF PUNE, MAHARASHTRA, INDIA - ABHIJIT GHADGE; SURESH KHADKE; SHUBHANGI HARKE; AMRUTA KAKADE; SUYASH PAWAR; UJWALA SHINDE; OMKAR KULKARNI; ANIKET A KUVALEKAR (International Journal of Pharma and Bio Sciences, 2013)
India has earned a dubious distinction of global diabetes capital. In this view, the present study was designed to assess awareness level of diabetes among the population of western Maharashtra. A cross-sectional study was carried out in and around Pune City. Normoglycemic adult Indian citizens were included in the study. About 49% of the population belonged to a group reporting increased incidence of type 2 diabetes mellitus (20-30 yrs.). With access to specialist treatment and income of individuals being positively correlated (r2=0.8), awareness about regular health check-up was quite low (20%-35.71%). The 12% of subjects, who never had medical check-up, had at least two symptoms of metabolic disorder and 30% of these had family history of type 2 diabetes. Literacy level and knowledge about different methods of blood glucose checking were positively correlated (r2=0.96). About 60% of the survey population believed that sweets or sugar intake causes diabetes. The study indicates an urgent need for raising awareness about this metabolic disorder in general population through all possible means to mitigate future burst and epidemiological burden.